Implementasi Metode Tahfidzul Kutub Alfiyah Ibnu Malik dalam Meningkatkan Pemahaman Nahwu Santri - Robi Gunawan (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the implementation of the Tahfidzul Kutub method in memorizing the book Alfiyah Ibnu Malik to improve students’ understanding of Arabic grammar (nahwu) at Darul Muta'alimin Islamic Boarding School, as well as to identify its supporting and inhibiting factors. This research employs a qualitative approach with a descriptive study design. Data were collected through participatory observation, in-depth interviews with the head of the boarding school, teachers (ustadz), and students, as well as documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results show that the implementation of the Tahfidzul Kutub method is carried out through systematic stages: talaqqi/bandongan (teacher-led reading), memorization (tikrar), submission (sorogan), review (muroja'ah), and periodic evaluation. This method has proven effective in improving students’ understanding of nahwu, as reflected in their increased ability to memorize verses, read classical Islamic texts (kitab kuning), and analyze sentence structures (i‘rab) up to the analytical level in Bloom’s taxonomy. Supporting factors include a conducive boarding school environment and the competence of the teachers, while inhibiting factors include differences in cognitive abilities and students’ consistency in conducting muroja'ah.